Phra Paisal Visalo’s Ideas: Some Reflections on Liberty, Equality and Buddhism in Contemporary Thai Society - Saisaeng, Bordin (Thai Journal of East Asian Studies, 2019)
This article aims to argue that the thoughts on liberty and equality, the foundation of democratic movements over decades, had effects on Buddhist values and ways of thinking in the Thai society. By focusing specifically on Phra Paisal Visalo, it found that he did not only accept such thoughts, but also tried to make them go along with Buddhist concepts. Nonetheless, as Phra Paisal Visalo demonstrated, liberty and equaility, riding the wave of consumersim in Thailand, also created moral concerns, and had negative impacts on Buddhism and the Thai society as well.